Sistem Informasi Pemantauan Dan Evaluasi Kinerja Karyawan Berdasarkan Penilaian Metode 360-DEGREE - Priambodo, Raditya; Sagirani, Tri; Suhandiah, Sri (Jurnal JSIKA, 2012)
Performance appraisal is the one of way to know how far they give their best performance to their company. In this current time, the performance appraisal at GGF & Country Club Surabaya which only do by the manager have less of objectivity. Except that, there are no process for observation and evaluate the result of performance appraisal which make the company feel difficult to know about the employee’s development. 360-Degree method is the one of performance appraisal method which have the focus point for the rater. The appraisal haven’t done only by the manager, but also do by their subordinates, their peers, and also by their self. The result from this process will be easy to do the observation in the graphic format. The evaluation will be given by the company based on the value’s representation which shown by the graphic of performance appraisal’s result. With the function of Monitoring and Evaluation Information System Based On 360-Degree Appraisal Method, hopefully the appraisal will have the higher of objectivity because the result already given by many rater surround the rate. Except that, with the monitoring process make the company easy to know the increase or decrease from their employee’s performance to give the evaluation. Keywords : Performance Appraisal, 360-Degree Method, Performance Monitoring, Performance Evaluation